Plea Bargaining Sebagai Pembaharuan Hukum Acara Pidana Berdasarkan Rancangan Undang-Undang KUHAP (RUU KUHAP) - Husin, Nabilla Callosa; Husin , Naylla Shabilla Callistha (Faculty of Law, Universitas Lampung, 2024)
The criminal justice process in Indonesia is characterized by lengthy proceedings, significant costs, and a growing prison population, highlighting the need for new policies to address these challenges. The adoption of the plea-bargaining concept, prevalent in common law jurisdictions, offers a potential solution for the Indonesian criminal justice system. Article 199 of the Draft Law on Criminal Procedure introduces a similar concept, allowing defendants who admit guilt to crimes punishable by no more than seven years in prison to have their cases transferred to a shorter trial process. This normative juridical research employed both statutory and conceptual analyses to evaluate the relevance of plea bargaining in the Indonesian context. It aims to assess whether the plea bargaining provisions in Article 199 of the Draft Criminal Procedure Code align with the principles of simplicity, speed, and cost-effectiveness, and whether they conform to Pancasila, the foundational ideology of Indonesia.